Challenges and Opportunities of Challenges Sustainable Development: Case of Mozambique (Global Journal of Human-Social Science, 2023)
This paper aims to analyze the challenges and opportunities in implementing the Sustainable Development Goals in Mozambique in the Social Economic and Environmental areas In order to provide the reader with an insight into how International Development Cooperation specifically the SDGs can pose challenges in countries whose stages of national development are different for the well-being of the global community In addition the challenges can be transformed into opportunities that international agreements provide to developing countries for their own development and consequently for the global good The analysis is made according to the models of International Development Cooperation as it provides a holistic view of the history of international cooperation from the traditional and modern perspective with regard to the SDGs The approach takes into account the situation of poverty COVID-19 natural disasters and the other problems that plague the international system in general and Mozambique in particular
Keywords: sustainable development goal; challenges; opportunities; mozambique